Bacteria do not incorporate β-N-methylamino-l-alanine into their proteins. (August 2015) - van Onselen, Rianita; Cook, Niall A.; Phelan, Richard R.; Downing, Tim G.
Abstract: β-N-methylamino-l -alanine (BMAA), is commonly found in both a free and proteinassociated form in various organisms exposed to the toxin. The long latency of development of neurodegeneration attributed to BMAA, is hypothesized to be the result of excitotoxicity following slow release of the toxin from protein reservoirs. It was recently suggested that these BMAA-protein associations may reflect misincorporation of BMAA in place of serine, as occurs, for example, when canavanine misincorporates in place of arginine. We therefore compared BMAA and canavanine toxicty in various bacterial species, and misincorporation of these amino acids into proteins in a bacterial protein expression system. None of the bacterial species showed any physiological stress responses to BMAA in contrast to the growth reduction observed when cultures were incubated in media containing canavanine. LC-MS analysis confirmed uptake of BMAA from growth media. However, after immobilized metal affinity chromatography and SDS-PAGE purification of proteins produced in an E scherichia coli expression system, no BMAA was detected by either LC-MS or LC-MS/MS analysis using two derivatization methods, or by orbitrap MS of trypsin digests of the protein. We therefore conclude that BMAA is not misincorporated into proteins in bacteria and that the observed BMAA-protein association in bacteria is superficial. Highlights: BMAA is not toxic to prokaryotes. BMAA does not misincorporate in prokaryotes. BMAA removal from proteins does not require hydrolysis.